Methanol production from CO2 reduction over Ni/TiO2 catalyst - Athikaphan, Pakpoom; Neramittagapong, Sutasinee; Assawasaengrat, Pornsawan; Neramittagapong, Arthit (My University, 2020)
Photocatalytic reduction of carbon dioxide into methanol fuel over the Ni-doped TiO2 catalyst has been investigated. The experiments were carried out in a 50 ml batch reactor under UV irradiation. Ni/TiO2 photocatalysts were prepared by an impregnation method. The properties of the catalyst were characterized by X-ray photoelectron spectroscopy (XPS), UV–Vis diffuse reflectance (UV–DR). Moreover, the effect of reaction time and Ni loading on the methanol conversion were investigated. The result indicated that the maximum of methanol production was obtained after the irradiation of 3 h and slightly reduced due to the methanol oxidation process. The Ni loading catalyst showed the higher methanol concentration than that over undoped TiO2 because Ni could trap the electron during irradiation and reduce electron–hole pair recombination by the p–n junction of TiO2. The highest methanol production rate of 272.45μmol/gcat was obtained over 4% wt Ni/TiO2 catalyst, which was 20 times higher methanol production rate than that over the commercial TiO2 catalyst (P25). Moreover, the stability of catalysts could be recycled four times with high activity of CO2 reduction to methanol. Therefore, 4% wt. Ni/TiO2 catalyst, low cost, showed better potential and activity in reducing CO2 emission to the environment.
Keywords: Artificial photosynthesis; Impregnation; Ni metal; Preparation of catalyst; Renewable energy